2017
DOI: 10.1117/1.jbo.22.2.026006
|View full text |Cite
|
Sign up to set email alerts
|

Examiner’s finger-mounted near-infrared spectroscopy is feasible to analyze cerebral and skeletal muscle oxygenation in conscious Chihuahuas

Abstract: , "Examiner's finger-mounted nearinfrared spectroscopy is feasible to analyze cerebral and skeletal muscle oxygenation in conscious Chihuahuas," J. Biomed. Opt. 22(2), 026006 (2017), doi: 10.1117/1.JBO.22.2.026006. Abstract. To measure regional saturation of oxygen (rSO 2 ) of hemoglobin and total hemoglobin index (HbI) in the brain (through the molera of the head) and skeletal muscle (musculus gracilis) of conscious Chihuahua dogs using an examiner's finger-mounted near-infrared spectroscopy (NIRS) device, To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Our previous study demonstrated that the brain rSO 2 values of healthy Chihuahuas at rest were approx. 60% (Hiwatashi et al 2017), suggesting that there is room for further study regarding potential heterogeneity of cerebral oxygen levels between these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that the brain rSO 2 values of healthy Chihuahuas at rest were approx. 60% (Hiwatashi et al 2017), suggesting that there is room for further study regarding potential heterogeneity of cerebral oxygen levels between these species.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, biophotonics approaches have been used to examine skin and subcutaneous tumors and to predict the prognosis of lymphoma (Cugmas and Spigulis 2019). We recently demonstrated that an examiner's finger-mounted NIRS device is feasible to analyze the oxygenation revels of brain and skeletal muscles in conscious Chihuahua dogs in a study of microcirculatory physiology among companion animals (Hiwatashi et al 2017). In that study, we proposed that Chihuahuas are suitable models for measuring the oxygenation levels of the brain due to the existence of the skull's molera in this breed.…”
Section: Introductionmentioning
confidence: 99%
“…The potential future work in veterinary medicine can be an evaluation of patients with trauma, sepsis, and surgical diseases, and to detect occult shock 25 . Additionally, cerebral and skeletal muscle oxygenation (regional saturation of oxygen (rSO 2 ) and total hemoglobin index (HbI)) was measured by finger-held NIRS device in small dogs (Chihuahua) 32 . Measuring oxy-and deoxy-hemoglobin with functional NIRS (fNIRS) can observe canine behavior changes 33 .…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Computational modeling in the literature [5][6][7][8][9][10][11][12][13][14] was used to determine design parameters and efficacy of detection and phantom studies [7,8,11,[15][16][17][18][19] were used to test prototypes. Pre-clinical [20][21][22][23] and clinical studies [7,[24][25][26][27][28] were performed to determine overall feasibility with the realistic conditions that transabdominal fetal pulse oximetry might encounter.…”
Section: Introductionmentioning
confidence: 99%